Co-construcción de soluciones barriales participativas, caso de estudio: “barrio San Vicente Bajo” parroquia Carigán del cantón y provincia de Loja, periodo abril - septiembre 2022 - Torres Guachisaca, Lady Jimena (2023)
The Co-construction of participatory neighborhood solutions project focused on contributing to the development of effective solutions in the San Vicente Bajo neighborhood, through the implementation of participatory, independent and democratic processes, aimed at promoting the organization and integration of the management and the residents, it also contributes to the identification of existing problems, so the theory of the ladder of citizen participation was analyzed to see the level of participation within the neighborhood. The methodology used for the present project is action research, the tools used are observation sheets, surveys, interviews, organizational charts, SWOT diagnosis, gravity matrix -urgency, problem trees and means and purposes, participatory workshop and the neighborhood action plan, through these, it was possible to identify three problems that need to be solved, so it was necessary to make an action plan for what is implemented in a given time and thus solve the problems. The results show that in the neighborhood there is little leadership ability, as well as little citizen participation, which does not allow for good organization and neighborhood integration, infrastructure and environmental problems were also identified.